1981
DOI: 10.1177/016502548100400202
|View full text |Cite
|
Sign up to set email alerts
|

German Children's Behavior Towards Their Mothers at 12 Months and Their Fathers at 18 Months in Ainsworth's Strange Situation

Abstract: Fourty-nine 12 months old children and their mothers were videotaped in Ainsworth's Strange Situation. Fourty-six of them were videotaped again in the same situation at 18 months with their fathers. Quality of attachment was determined by using Ainsworth's criteria. Fewer children had 'secure' relationships to their parents than in comparable U.S. samples. There was no correlation between infant-mother and infant-father quality of attachment relationship. The results are discussed in terms of parental attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
1
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(85 citation statements)
references
References 11 publications
3
79
1
1
Order By: Relevance
“…Therefore, with respect to the effect of rating across laboratories, the Bielefeld sample can be conceived as comparable to the U.S., Israeli, and Swedish samples. The final classifications made, in addition to ratings of preseparation episodes, perfectly matched the original classifications made by Grossmann et al, (1981) .…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, with respect to the effect of rating across laboratories, the Bielefeld sample can be conceived as comparable to the U.S., Israeli, and Swedish samples. The final classifications made, in addition to ratings of preseparation episodes, perfectly matched the original classifications made by Grossmann et al, (1981) .…”
Section: Methodssupporting
confidence: 55%
“…Last, we expected the Strange Situation to be robust against procedural variations that have been introduced into cross-cultural attachment research. More specifically, it was hypothesized that the size of the playroom (the former Federal Republic of Germany, i.e., Grossmann et al, 1981 ), age of subjects (the Netherlands), and a stranger sociability test preceding the Strange Situation procedure (United States, Sweden, and Israel) would not be related to systematic differences in Strange Situation behavior. To address the issue of cross-cultural differences in primary appraisals as well as the influence of procedural variations, we decided to compare infants' behavior toward both the mother and the stranger during the preseparation episodes in all available samples from several different cultures rather than focus on a few previously discussed samples (i.e., Israel, Japan, and the former Federal Republic of Germany).…”
mentioning
confidence: 99%
“…This network approach should be looked upon differently from previous findings in several stuclies in which it was shown that the quality of attachment relationships with different caretakers was discordant (Lamb, 1977;Main and Weston, 1981;Grossmann, Grossmann, Huber, and Wartner, 1981;Sagi and others, 1985). Although Sagi and othcrs (1985) handled the data in tcrms of dependence without suggcsting implications for the Integration of these discordant intcrnal working models (Brctherton, 1985), the network approach can be viewcd äs a new move toward a more complcx consideralion o( how different intcrnal working models of attachment relationships might integrale and relate to other indices of development.…”
Section: Resultsmentioning
confidence: 79%
“…One of the most salient and highly replicated findings is that the quality of attachment relationships with different caretakers is often discordant. The discordance of secure, resistant, and avoidant patterns with respect to father and to mother has been shownby Lamb (1977), Main and Weston (1981), Grossmann, Grossmann, Huber, and Wartner (1981) and Sagi and others (1985). The same lack of concordance of attachment quality within a broader network of infantcaretaker relationships was found in Sagi and others (1985), Goossens andVan IJzendoorn (1990), andKrentz (1983) for infant-parent and infant-professional caregiver relationships.…”
Section: Multiple Caretaker Paradoxmentioning
confidence: 92%
“…La propension à la perturbation et à la réactivité au cortisol prédit l'intensité des pleurs durant les séparations dans la Situation Etrange à 9 mois (Gunnar, Mangelsdorf, Larson, et Hertsgaard, 1989 ; Spangler, et Grossmann, 1993). Toutefois, ce niveau de perturbation ne prédit pas la qualité de l'organisation de l'attachement ou la facilité Comme la sécurité vis-à-vis de la figure d'attachement est en relation avec l'histoire interactive de la dyade, le même enfant peut développer un attachement sécure avec un des parents et un attachement insécure avec l'autre (Grossmann, Grossmann, Huber, et al, 1981 ;Main et Weston, 1981), ou passer d'un attachement insécure vers un attachement sécure avec le même parent quand surviennent des changements significatifs dans les circonstances de vie (Egeland et Farber, 1984).Il est à souligner que certains bébés peuvent se montrer très difficiles et mettre en péril le système de caregiving . Toutefois, quand un soutien aux parents est donné de façon adéquate, les soins sensibles permettent de mieux affronter les difficultés de ces enfants (Crokenberg, 1981 ;Susman-Stillman, Kalkowske, et Egeland, 1996).…”
unclassified